GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 14551 species occurrences available in GBIF matching the query: TaxonKey: Eumomota superciliosa (Sandbach, 1837). The dataset includes 14551 records from 61 constituent datasets: 2 records from SUI Vertebrate Collection. 2 records from Canadian Museum of Nature Bird Collection. 12 records from naturgucker. 5 records from Naturalis Biodiversity Center (NL) - Aves. 18 records from Colección nacional de zoología. 38 records from UMMZ Birds Collection. 12 records from CUMV Bird Collection (Arctos). 62 records from KUBI Ornithology Collection. 112 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 2 records from Evaluación y monitoreo de manglar en la Reserva de la Biósfera Los Petenes con énfasis en criterios de sustentabilidad y desarrollo. 2 records from Bird Collection. 17 records from CNAV/Coleccion Nacional de Aves. 1 records from SDNHM Birds Collection. 19 records from MLZ Bird Collection (Arctos). 13072 records from EOD - eBird Observation Dataset. 3 records from CAS Ornithology (ORN). 78 records from Field Museum of Natural History (Zoology) Bird Collection. 1 records from Aves de México I. 27 records from MVZ Bird Collection (Arctos). 64 records from AMNH Bird Collection. 1 records from CHAS Ornithology. 92 records from Inventario avifaunístico de las áreas focales Zoh-Laguna y La Montaña en el corredor biológico mesoamericano Sian Ka'an- Calakmul, México. 6 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 3 records from DMNH Birds. 23 records from UWBM Ornithology Collection. 62 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 20 records from DMNS Bird Collection (Arctos). 74 records from Museum of Comparative Zoology, Harvard University. 1 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 1 records from Queensland Museum provider for OZCAM. 4 records from CRCM Vertebrate Collection. 3 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 1 records from Aves MZS. 5 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 1 records from Baillon Collection. 4 records from Inventario nacional de especies vegetales y animales de uso artesanal. 1 records from ISU Birds. 1 records from HSU Wildlife Birds. 1 records from MSB Bird Collection (Arctos). 1 records from South Australian Museum Australia provider for OZCAM. 32 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 86 records from iNaturalist Research-grade Observations. 1 records from Zoology (Museum of Evolution - Uppsala). 28 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 22 records from Macaulay Library Audio and Video Collection. 38 records from LSUMZ Birds Collection. 6 records from UAZ Bird Collection. 187 records from Atlas de las Aves de México: Fase II. 37 records from ORN. 2 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 2 records from MZFC/Coleccion de Aves. 56 records from UCLA Donald R. Dickey Bird and Mammal Collection. 1 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 3 records from LSUMZ Bird Tissues. 4 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 19 records from Collection Aves (bird skins) SMF. 12 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 39 records from WFVZ Bird Collections. 45 records from CM Birds Collection. 54 records from NMNH Extant Specimen and Observation Records. 23 records from LACM Vertebrate Collection. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences